Determinants of Anemia Among Patients with Chronic Kidney Disease: A Systematic Review of Empirical Evidence - Prapaiwong P; Ruksakulpiwat S; Jariyasakulwong P; Kasetkala P; Puwarawuttipanit W; Pongsuwun K (Journal of Multidisciplinary Healthcare)
Prapatsinee Prapaiwong, Suebsarn Ruksakulpiwat, Pawitra Jariyasakulwong, Piyoros Kasetkala, Wimolrat Puwarawuttipanit, Kewalin Pongsuwun Department of Medical Nursing, Faculty of Nursing, Mahidol University, Bangkok, ThailandCorrespondence: Suebsarn Ruksakulpiwat, Department of Medical Nursing, Faculty of Nursing, Mahidol University, 2 Wanglang Road, Siriraj, Bangkok Noi, Bangkok, 10700, Thailand, Email suebsarn.ruk@mahidol.ac.thObjective: This systematic review aimed to identify and synthesize empirical evidence regarding determinants of anemia among patients with chronic kidney disease (CKD) to inform clinical management and guide future research.Methods: A comprehensive search of six electronic databases (PubMed, MEDLINE, ScienceDirect, Scopus, Web of Science, Google Scholar) was conducted for studies published from 2019 to 2024, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal checklists tailored to each study design, and data synthesis was performed using convergent thematic analysis.Results: Of 2269 records initially identified, 21 studies met inclusion criteria. Most studies originated from China (33.3%), employed cross-sectional designs (66.6%), and were hospital-based. Overall methodological quality was moderate to high, with JBI scores ranging from 69.23% to 100% (mean = 86.48%); notably, 47.6% of studies achieved a perfect quality score. Seven key themes emerged: 1) demographic and personal characteristics, 2) comorbidities, 3) duration of dialysis treatment, 4) kidney function, 5) biomarkers and metabolic ions, 6) geographic disparities, and 7) stimulation interventions (including stimulating agents, supplements, and exercise). Our review highlights that comorbidity (eg, diabetes mellitus, low BMI), declining kidney function, prolonged dialysis duration, and biomarkers such as calcium, phosphorus, ferritin, and inflammatory markers were significantly associated with anemia. Geographic disparities highlighted greater anemia prevalence in rural populations.Conclusion: This review underscores multifaceted determinants of anemia in CKD, emphasizing comprehensive assessment and targeted interventions. Future research should explore individualized strategies addressing these diverse factors.Keywords: chronic kidney disease, anemia, risk factors, comorbidities, dialysis, biomarkers, geographic disparities, systematic review